2021
DOI: 10.32598/hms.27.1.3316.1
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Disability and Its Relationship With the Demographic Characteristics of the Elderly in Gonabad City, Iran, in 2019

Abstract: Aims: Disability reduces the independence and quality of life in the elderlies and it increases their independence and causes increased need of support, more admittance in nursing homes and early death. The aim of this study was to examine the prevalence of disability and its relationship with the demographic characteristics. Methods & Materials: This cross-sectional (descriptive-analytical) study was performed on 470 elderly people aged 60 and over living in Gonabad by random stratified sampling. Data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…For instance, Mozafari et al (2016) showed that most older adults experience low to moderate levels of disability [ 37 ]. However, Baghery Kakhki et al (2020) found that older adults have very low levels of disability [ 25 ]. Additionally, Jafari et al (2018) reported that most older adults experienced moderate to severe disability [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Mozafari et al (2016) showed that most older adults experience low to moderate levels of disability [ 37 ]. However, Baghery Kakhki et al (2020) found that older adults have very low levels of disability [ 25 ]. Additionally, Jafari et al (2018) reported that most older adults experienced moderate to severe disability [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, family members were the primary source of perceived social support for these older adults. Baghery Kakhki et al (2020) and Adib-Hajbaghery et al (2009) reported that self-care had the lowest level of disability among older adults [ 25 , 26 ]. Similarly, Noei et al (2017) found that self-care had the lowest levels of disability among older men [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a population based study in Tehran, the prevalence of disability among Iranian older adults over 60 years old was 11% in which hearing loss was the most common type of disability (85%). In another study on 470 elderly people aged 60 and over, in Gonabad city in Iran, 40.6% of the elderly experienced low disability, 15.2% had moderate disability and 8.6% face severe disability [8].…”
Section: Introductionmentioning
confidence: 96%